Visualization analysis of research on climate innovation on CiteSpace - Cheng, Zhice; Xie, Yuchen; Wen, Huwei (Frontiers in Environmental Science, 2022)
Climate change has brought great challenges to global sustainability, but only few research achievements in innovation for climate change mitigation and adaptation have been reported. This study aims to identify the current research status and trends in climate innovation via CiteSpace visual analysis. We searched for published papers (up to 2021) in the core repository of Web of Science by using the theme of innovation for climate change mitigation and adaptation. Using the collected articles, we conducted co-authorship analysis, co-citation analysis, and keyword co-occurrence analysis and found that the main contributors are from America, England, and China. Moreover, climate innovation has an interdisciplinary knowledge source, and its main research frontier focuses on the design of policies for energy efficiency improvement and new energy technologies. These results point out some directions for further research on climate innovation and outline the knowledge structure in this field, thereby addressing the lack of studies on such topic. By analyzing the lineage of research developments, it is found that energy technology and energy efficiency would be the main research hotspots in climate innovation in the future, and relevant policies also need to strengthen incentives for research in this area. This study is particularly helpful for those researchers who are interested in climate innovation and can subsequently contribute to the long-term development of various research directions in this field, to the formulation of climate change mitigation and adaptation policies, and to the sustainable development of human society.